Chloroplast phylogenomics provides new evidence for reevaluating the taxonomic placement of medicinal Agapetes - Wang, Jindong; Li, Baizhu; Liu, Yunjing; Li, Yu; Yi, Yin; Xie, Wei; Tang, Xiaoxin (Frontiers in Plant Science, 2025)
Species of Agapetes are recognized for their radish-like tubers, which possess significant medicinal properties. Resolving the long-standing phylogenetic controversies between Agapetes and its relatives is crucial for facilitating the utilization of this genus. However, the scarcity of molecular data has persistently constrained such investigations. In this study, we generated the first high-quality chloroplast (cp) genome assemblies for three pharmacologically important Agapetes species: A. malipoensis, A. guangxiensis, and A. obovata, with genome sizes of 172,729, 176,291, and 180,574 bp, respectively. Phylogenetic analyses based on both complete chloroplast genomes and nuclear internal transcribed spacer (ITS) sequences supported the monophyly of Agapetes and Vaccinium, with bootstrap values of 100% and 63%, respectively. More intriguingly, the chloroplast phylogeny placed the Agapetes clade nested within Vaccinium. Moreover, the ITS phylogeny revealed that species of Agapetes were intermixed with those of Vaccinium. This intermixed pattern was further supported by hierarchical clustering based on relative synonymous codon usage (RSCU) and the abundance of repetitive sequences, including simple sequence repeats (SSRs) and dispersed repeats. Species of the two genera exhibited no significant differences in other chloroplast genomic features, including proportions of protein-coding genes and non-coding regions, GC content across all quadripartite structural regions, IR boundary shift, and tandem repeats. These findings provide novel molecular evidence supporting the taxonomic merger of the medicinally important genera Agapetes and Vaccinium. This work establishes a critical foundation for future investigations into the evolutionary origins of medicinal traits, pharmaceutical exploration, and the precise species delimitation of Agapetes and Vaccinium.